Investigation of the potential predictive value of flow-volume curve changes in patients with obstructive sleep apnea syndrome - Akkuş, Fatma Arzu; Yosunkaya, Şebnem (The European Research Journal, 2025)
Objectives: The relationship between pulmonary function tests (PFT) performed while awake and sleep-related breathing disorders is not yet well defined. This study aimed to examine the potential of flow-volume curve abnormalities in assessing both the presence and severity of obstructive sleep apnea syndrome. Methods: This retrospective study reviewed medical records of patients evaluated for suspected obstructive sleep apnea syndrome (OSAS) between May 2011 and April 2013. Among 141 patients with available PFT, 99 were diagnosed with OSAS, and 42 were normal based on polysomnography results. Patients were classified into OSAS and control groups, and pulmonary function parameters, including flow-volume curve features, were analyzed. Results: Of the OSAS patients, 80 (80.8%) were male, while 22 (52.4%) males were present in the control group, which consisted of patients not diagnosed with obstructive sleep apnea syndrome. Among pulmonary function test parameters, the ratio of maximal mid-expiratory flow to forced vital capacity (FEF25-75/FVC) was lower in the obstructive sleep apnea syndrome group than in the control group (P<0.05). Patients with the sawtooth sign showed significantly higher apnea-hypopnea index, apnea-hypopnea index during rapid eye movement sleep, and total apnea scores (P<0.05). The presence of sawtooth signs in the flow-volume loop was useful for identifying more severe cases of obstructive sleep apnea syndrome. Conclusions: The complex pathophysiology of obstructive sleep apnea syndrome complicates the identification of patients who need polysomnography. Flow-volume curve abnormalities, indicating airway instability in the upper respiratory tract, are common in these patients and may serve as early indicators of obstructive sleep apnea syndrome.